The relationship between radiographic changes and performance outcome in Quarter Horse cutting horses - Barrett Frisbie, Myra Frances, author; McIlwraith, C. Wayne, advisor; Park, Richard D., committee member; Kawcak, Christopher E., committee member; Werpy, Natasha, committee member (Colorado State University. Libraries, 2010)
Reason for Performing the Study: Radiographic repositories are become increasingly popular in multiple disciplines as a screening tool prior to sale. However, the importance of the radiographic findings must be objectively assessed relative to potential significance. While studies have been done to correlate survey radiographic findings with performance outcomes in Thoroughbreds, no such published study exists in Quarter Horses. This paper serves as part two of a study examining the relationship between radiographic changes in survey radiographs relative to objective performance outcomes in Quarter Horse cutting horses. Objectives: The goal of this study is to better clarify the potential significance of radiographic changes on repository radiographs relative to performance. This in turn will allow veterinarians and their clients to make more objective, informed decisions prior to purchase about the potential implications of various radiographic changes. Methods: Radiographic changes of 436 Quarter Horses, which were quantified in a previous paper (Contino et al 2009), were compared to objective performance outcome parameters. The parameters were: 1) likelihood of competing, 2) likelihood of earning money as a three year old, four year old and as a three and four year old combined, 3) average amount of money earned as a three year old, four year old and as a three and four year old combined. Mailed questionnaires and phone calls to owners of horses that did not earn money were used to try to determine why the horse had no recorded earnings. Results: When the tarsometatarsal (TMT) and distal intertarsal (DIT) joints were examined together, the presence of mild (grade 2) osteophytes, which affected 19% of the horses, was associated with reduced chance of competing, earning money and mean money earned. Very mild and mild osteophytes of the third and central tarsal bone assessed individually at the level of the TMT and DIT also had some significant effects in multiple performance outcome categories. The presence of thickening of the dorsal cortex of the hind second phalanx as well as osteophytes as this location was associated with an increased likelihood of earning money. Several other potentially significant findings are reported but affect a relatively small number of the horses included in the study. Radiographic changes of the medial femoral condyle of the stifle were not significantly associated with performance outcome. Conclusions: Many radiographic changes were not found to be significantly associated with performance outcome. However, some mild changes were associated with decreased performance. In addition, some radiographic changes were correlated with improved performance outcome. Potential Relevance: The findings of this study can be used to help veterinarians make more objective assessments of survey radiographic findings prior to sale. This research helps lay the groundwork for further investigations of the significance of survey radiographic findings in individual breeds and disciplines.
Keywords: radiograph repository; performance outcome; orthopaedics; cutting horse; equine; Cutting horses; Cutting horses -- Performance records; Veterinary radiography; Quarter horse